The transplant team's support of kidney transplant recipients to take their prescribed medications: a collective responsibility. Issue 15 (6th June 2016) - Williams, Allison; Low, Jac Kee; Manias, Elizabeth; Crawford, Kimberley
Abstract : Aims and objectives: To obtain an understanding of how health professionals support the kidney transplant patient to take their medications as prescribed long term. Background: Kidney transplantation requires stringent adherence to complex medication regimens to prevent graft rejection and to maintain general well‐being. Medication nonadherence is common in kidney transplantation, emerging in the first few months post‐transplantation, leading to poor patient outcomes. Design: Exploratory qualitative design. Methods: Five focus groups were conducted with a total of seven renal nurse transplant coordinators, two renal transplant nurse unit managers, seven nephrologists, seven pharmacists, four social workers, and one consumer representative representing all five hospitals offering adult kidney transplantation in Victoria, Australia in 2014. The views of two general practitioners who were unable to attend the focus groups were incorporated into the data set. All data underwent thematic analysis. Results: Analysis revealed that adherence was a collective responsibility involving the whole of the transplant team and the patient via education blitz in hospital, identifying and managing nonadherence, promotion of self‐advocacy, and the partnership between the patient and health professional. Patients were directed how to take their complex medications to be self‐empowered, yet the partnership between the patient and health professional limited the patient's voice. Conclusion: Although medication adherence was a collective responsibility, communication was often one‐way chiefly as a result of staffing and time constraints, hindering effective partnerships necessary for medication adherence. Expert skills in communication and adherence counselling are necessary to identify barriers affecting medication adherence. Patients need to be systematically screened, prepared and supported long‐term within an accommodating healthcare system for the reality of caring for their transplanted kidney. Relevance to clinical practice: Kidney transplant recipients require systematic preparation and quality long‐term follow‐up to adhere to their prescribed medications.